A Novel Nuclear Member of the Thioredoxin Superfamily - Laughner, Beth J. (American Society of Plant Physiologists, 1998)
We describe the isolation and characterization of a cDNA encoding maize (Zea mays L.) nucleoredoxin (NRX), a novel nuclear protein that is a member of the thioredoxin (TRX) superfamily. NRX is composed of three TRX-like modules arranged as direct repeats of the classic TRX domain. The first and third modules contain the amino acid sequence WCPPC, which indicates the potential for TRX oxidoreductase activity, and insulin reduction assays indicate that at least the third module possesses TRX enzymatic activity. The carboxy terminus of NRX is a non-TRX module that possesses C residues in the proper sequence context to form a Zn finger. Immunolocalization preferentially to the nucleus within developing maize kernels suggests a potential for directed alteration of the reduction state of transcription factors as part of the events and pathways that regulate gene transcription.